Strength and conditioning for Brazilian jiu-jitsu - Jones, N. B.; Ledford, E. (Strength and Conditioning Journal, 2012)
Brazilian jiu-jitsu is a grappling sport that combines aspects of wrestling and judo as well as its own specific techniques. This article discusses how to design an appropriate strength and conditioning program for the sport. It covers the strength, power, endurance, and flexibility needs of the jiu-jitsu athlete and injury prevention.